Propuesta de plan de mejora para el área de recreación turística en la Finca “Los Alpes Verdes” del cantón Buena Fe, provincia Los Ríos, 2022 - Bone Bone, Gilda Alejandra (2022)
The present research project carried out in the Patricia Pilar parish, its main purpose is to make known the importance that tourism resources have within the area, the place maintains a large amount of natural resources, which can be exploited through the proposed creation of the tourist area in the Finca "Los Alpes Verdes", with the aim of promoting sustainable